Effectiveness of I’m Learning for achieving quality learning environments: Impact and implications from three country pilots - Zook, Lisa; Ryall, Cameron (Nordic Journal of Comparative and International Education (NJCIE), 2021)
From 2013 to 2017, Save the Children Norway tested the hypothesis that a global framework could be used to empower locally driven solutions within the education sector. It did so by galvanizing support and aligning stakeholders to common goals articulated through the Quality Learning Environment Framework but allowing each community context to determine its own path for achieving those goals. This article explores the effectiveness and impact of these projects across the three pilot countries of Cambodia, Uganda, and Zimbabwe as defined by the original project goals, outcomes, and objectives. Reflecting on both qualitative and quantitative data gathered throughout the life of the project, the article speaks to project impact and achievements as well as operational findings including commonalities and differences between the three pilot projects and keys to success. It outlines lessons learned across the programming sites and in doing so it explores the role of a large International Non-Governmental Organization as a catalyst for change. Finally, it discusses the rigorous research and reporting framework driven by funders and development agencies, the rigidity of which struggled to capture the emergent nature of locally driven solutions.